MARii, UMP ink MoU to expand technology expertise through new academic programmes - UMP, PNC (2019)
A Memorandum of Understanding (MoU) was signed between Universiti Malaysia Pahang (UMP) and Malaysia Automotive, Robotics and IoT Institute (MARii) on November 18, 2019 at Kuala Lumpur.